KANNADA FOLK LITERATURE: A STUDY OF THE ORAL TRADITIONS AND CULTURAL SIGNIFICANCE - Naragund, Prakash N; Hatti, Shri. S.R.; Angadi, Dr. S.C. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Kannada folk literature is a rich and diverse repository of oral traditions, reflecting the cultural, social, and historical contexts of Karnataka. This study explores the significance of Kannada folk literature, examining its oral traditions, cultural relevance, and impact on contemporary society. Through a qualitative analysis of folk songs, stories, and legends, this research highlights the importance of preserving and promoting Kannada folk literature as a vital part of Karnataka’s cultural heritage.